Solid-state synthesis of NASICON (Na3Zr2Si2PO12) using nanoparticle precursors for optimisation of ionic conductivity - Christopher Phillips (Journal of Materials Science, 2019)
In this work, the effect of varying the size of the precursor raw materials SiO2 and ZrO2 in the solid-state synthesis of NASICON in the form Na3Zr2Si2PO12 was studied. Nanoscale and macro-scale precursor materials were selected for comparison purposes, and a range of sintering times were examined (10, 24 and 40 h) at a temperature of 1230 °C. Na3Zr2Si2PO12 pellets produced from nanopowder precursors were found to produce substantially higher ionic conductivities, with improved morphology and higher density than those produced from larger micron-scaled precursors. The nanoparticle precursors were shown to give a maximum ionic conductivity of 1.16 × 10−3 S cm−1 when sintered at 1230 °C for 40 h, in the higher range of published solid-state Na3Zr2Si2PO12 conductivities. The macro-precursors gave lower ionic conductivity of 0.62 × 10−3 S cm−1 under the same processing conditions. Most current authors do not quote or consider the precursor particle size for solid-state synthesis of Na3Zr2Si2PO12. This study shows the importance of precursor powder particle size in the microstructure and performance of Na3Zr2Si2PO12 during solid-state synthesis and offers a route to improved predictability and consistency of the manufacturing process.